العتبات النصية في كتاب الجسد حقيبة سفر للكاتبة غادة السمان - بن عمر, مردف, مباركة ايمان (Univercty of Eloued, 2020)
قد أولت الدراسات الأدبية والنقدية أهمية كبيرة لموضوع العتبات النصية داخل النص الأدبي ، من خلال تحديد المفهوم و الأنواع والوظائف مما سجلت حضورا لافتا في الدراسة النقدية حول التشكيل الدلالي والجمالي للعتبات خصوصا جانب العنونة. وذلك من خلال استدراج المتلقي (القارئ) لأغوار النص وخباياه المشفرة ، فكل عتبة من عتبات النص الأدبي تحمل عدة وظائف دلالية أمام القارئ من خلال الإغواء والإغراء ،التشويق والتحليل . حيث سعى بحثنا هذا كسائر البحوث العلمية في الغوص حول الموضوع " العتبات النصية " خاصة جانب عتبة العنوان التي تفرض سيطرتها على باقي العتبات الأخرى ومكونات النص الأدبي ، وما تحدثه من أثر بالغ لدى المتلقي . مما سمحت لنا الدراسة حول موضوع "العتبات النصية في كتاب الجسد حقيبة سفر " للكاتبة والأديبة السورية "غادة السمان " بالوقوف على العتبات النصية وذلك من خلال ضبط المفهوم اللغوي والإصطلاحي ،والوظائف الدلالية والجمالية المحدثة داخل النصوص الأدبية . انطلاقا من ربط العلاقة بين العتبات النصية والكتاب (الجسد حقيبة سفر ) ،التي كانت لها أثرا دلاليا وبعدا جماليا من Literary and critical studies have attached great importance to the subject of textual thresholds within the literary text, by defining the concept, genres and functions, which recorded a remarkable presence in the critical study of the semantic and aesthetic formation of thresholds, especially the heading aspect. And that is by luring the recipient (the reader) into the depths of the text and its encrypted mysteries. Each threshold of the literary text carries several semantic functions in front of the reader through seduction, temptation, suspense and analysis. Our research, like all other scientific researches, sought to dive into the topic of "textual thresholds", especially the aspect of the title threshold that imposes its control over the rest of the other thresholds and components of the literary text, and the great impact it has on the recipient. Thus, the study on the topic of "Textual Thresholds in the Book of the Body is a Travel Bag" by the Syrian writer and writer "Ghada Al-Samman" allowed us to identify the textual thresholds by controlling the linguistic and idiomatic concept, and the updated semantic and aesthetic functions within literary texts. Based on linking the relationship between textual thresholds and the book (the body is a travel bag), which had a semantic effect and an aesthetic dimension through the title threshold, the cover threshold, the introduction threshold, the dedication threshold, the threshold of internal addresses.
Keywords: االعتبات النصية الجسد حقيبة سفر